Toolbox for data, tools, and guidelines for monitoring, reporting, and verification of Greenhouse Gas (GHG) calculation in rice - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The toolbox has been developed to provide Spatial Data, Tools, and Guidelines to support MRV in rice, made publicly accessible on the GHG Mitigation homepage.